Tourette Syndrome Prevalence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The prevalence of Tourette syndrome in a mainstream school population (ages 13 to 14 years) in West Essex, England has been determined by parent, teacher, and pupil questionnaires, class observations to identify tics, and subject and parent face-to-face interviews, and reported from the Section of Epidemiology and General Practice, Institute of Psychiatry, Denmark Hill, London, UK.